To solve the expression \((-3) \div \left(\frac{3}{4}\right) \times \left(\frac{2}{7}\right) \times \left(-\frac{5}{16}\right) \div \left(\frac{5}{7}\right)\), we will simplify the expression step by step.
-
Divide by a fraction: Dividing by a fraction is the same as multiplying by its reciprocal. \[ (-3) \div \left(\frac{3}{4}\right) = (-3) \times \left(\frac{4}{3}\right) = -\frac{12}{3} = -4 \]
-
Substituting back into the expression: Now our expression looks like this: \[ -4 \times \left(\frac{2}{7}\right) \times \left(-\frac{5}{16}\right) \div \left(\frac{5}{7}\right) \]
-
Continuing with the division: \[ \div \left(\frac{5}{7}\right) = \times \left(\frac{7}{5}\right) \] So we can replace the division: \[ -4 \times \left(\frac{2}{7}\right) \times \left(-\frac{5}{16}\right) \times \left(\frac{7}{5}\right) \]
-
Multiplying the negative values: The product of two negative numbers is positive: \[ -4 \times \left(\frac{2}{7}\right) \times \left(-\frac{5}{16}\right) = 4 \times \left(\frac{2}{7}\right) \times \left(\frac{5}{16}\right) \]
-
Combining: \[ 4 \times \left(\frac{2}{7}\right) \times \left(\frac{5}{16}\right) \times \left(\frac{7}{5}\right) \]
-
Breaking it down: \[ = 4 \times \frac{2}{7} \times \frac{5}{16} \times \frac{7}{5} \] Notice that the \(5\)s cancel: \[ = 4 \times \frac{2}{7} \times \frac{7}{16} \]
-
Canceling the \(7\)s: \[ = 4 \times \frac{2}{16} \]
-
Calculate \( \frac{2}{16} \): \[ \frac{2}{16} = \frac{1}{8} \]
-
Final Multiplication: \[ = 4 \times \frac{1}{8} = \frac{4}{8} = \frac{1}{2} \]
Thus, the final result of the expression is \(\boxed{\frac{1}{2}}\).